A hope intervention for adolescents: a randomized controlled trial delivered by paraprofessionals - Scioli, Anthony; MacPherson, Nathan; Murphy, Rachel; Gooding, Tyler; Love, Micah; Lyons, Kathleen D.; Adachi-Mejia, Anna M. (Frontiers in Psychology, 2025)
IntroductionA workshop for adolescents was derived from an interdisciplinary model of hope. The workshop was created for delivery by professionals or lay helpers and is structured around the needs for attachment, survival, mastery, and spirituality.MethodsAdolescents, 13 to 17 years of age, received a five-week group intervention led by pairs of advanced psychology students. Hope, depression, anxiety, coping, and self-acceptance were assessed before and after the intervention. A delayed waitlist control group, matched for age, received identical outcome measures, also five-weeks apart. Group membership was randomly assigned.ResultsMore than three-quarters of the participants found the more left-brain writing exercises helpful, and nearly 85% rated the more right-brain reflections and meditative exercises favorably. Significant increases in hope as well as greater utilization of social coping methods and self-acceptance were found for the treatment group but not controls. Group participants (but not controls) also reported a significant reduction in depression. Anxiety levels were not impacted. Secondary analysis suggested that participant engagement and socioeconomic status may play a role in moderating the efficacy of this intervention.DiscussionThis relatively low-cost intervention offers new hope for counteracting the global increase in youth despair. The effect sizes obtained in this study compare favorably with outcome data for cognitive-behavioral treatments and a few available agency-centered hope interventions. There is a potential for broad impact via the implementation of an accessible training program as well as online deliveries in either synchronous or asynchronous modes.